Applicability of head space solid phase microextraction (HS-SPME) with polyethylene glycol (PEG) fibre for GC-MS determination of volatile fatty acids in aqueous samples - Faniband, Moosa Hassan (2010)
A method consisting of head-space solid phase micro extraction (HS-SPME) followed by gas chromatography coupled with mass spectrometry (GC-MS) was developed for determination of volatile fatty acids in wastewater. A new fibre polyethylene glycol (PEG) was evaluated for the sample preparation. This fibre is designed to show high sample capacity, faster mass transfer during extraction, shorter equilibrium times and faster desorption process. The developed method showed good sensitivity with comparable limit of detection (LOD) and limit of quantitation (LOQ) values. The selection of various parameters included extraction time, extraction temperature, sample volume and desorption conditions. The experimental results showed low detection limits ranging between 0.01 mg/L to 0.06 mg/L for different acids. The new fibre was found to be efficient towards acetic and propionic acid.